Driveline Infection in Left Ventricular Assist Device Patients: Effect of Standardized Protocols, Pathogen Type, and Treatment Strategy. Issue 12 (27th February 2022) - Lumish, Heidi S.; Cagliostro, Barbara; Braghieri, Lorenzo; Bohn, Bruno; Mondellini, Giulio M.; Antler, Karen; Feldman, Vivian; Kleet, Audrey; Murphy, Jennifer; Tiburcio, Melie; Fidlow, Kathryn; Jennings, Douglas; et al.
Abstract : Driveline infection (DLI) is common after left ventricular assist device (LVAD). Limited data exist on DLI prevention and management. We investigated the impact of standardized driveline care initiatives, specific pathogens, and chronic antibiotic suppression (CAS) on DLI outcomes. 591 LVAD patients were retrospectively categorized based on driveline care initiatives implemented at our institution (2009–2019). Era (E)1: nonstandardized care; E2: standardized driveline care protocol; E3: addition of marking driveline exit site; E4: addition of "no shower" policy. 87(15%) patients developed DLI at a median (IQR) of 403(520) days. S. aureus and P. aeruginosa were the most common pathogens. 31 (36%) of DLI patients required incision and drainage (I&D) and 5 (5.7%) device exchange. P. aeruginosa significantly increased risk for initial I&D (HR 2.7, 95% CI, 1.1–6.3) and recurrent I&D or death (HR 4.2, 95% CI, 1.4–12.5). Initial I&D was associated with a significant increased risk of death (HR 2.92 (1.33–6.44); P = 0.008) when compared to patients who did not develop DLI. Implementation of standardized driveline care protocol (E2) was associated with increased 2-year freedom from DLI compared to nonstandardized care (HR 0.36, 95% CI, 0.2–0.6, P < 0.01). Additional preventive strategies (E3&E4) showed no further reduction in DLI rates. 57(65%) DLI patients received CAS, 44% of them required escalation to intravenous antibiotics and/or I&D. Presence of P. aeruginosa DLI markedly increased risk for I&D or death. Conditional survival of patients progressing to I&D is diminished. Standardized driveline care protocol was associated with a significant reduction in DLI, while additional preventive strategies require further testing.